The gender gap of returns on education across West European countries - Concetta Mendolicchio; Thomas Rhein (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2011)
We study the returns on education in Europe in a comparative perspective. We extend the model of de la Fuente [(2003). Human Capital in a Global and Knowledgebased Economy. part II: Assessment at the EU Country Level. Report for the European Commission], by estimating the values of the relevant parameters for men and women and introducing several variables specifically related to maternity leaves and benefits. As a preliminary step, we evaluate the effect of education on the wage profile. We estimate the Mincerian coefficients for 12 West European countries using the EU-SILC data for 2007 and use them as input in the optimisation problem of the individual to calibrate the model. Finally, we analyse the impact and relevance of several public policy variables. In particular, we evaluate the elasticities of the returns to education with respect to unemployment benefits, marginal and average tax rates, maternity leave and childcare benefits. – – Wir untersuchen die Bildungserträge in Europa in vergleichender Perspektive. Wir erweitern dazu das Modell von de la Fuente [(2003). Human Capital in a Global and Knowledge-based Economy. part II: Assessment at the EU Country Level. Report for the European Commission], indem wir die relevanten Parameter für Männer und Frauen schätzen und einige Variablen für staatliche Leistungen bei Eltern- oder Erziehungsurlaub und für Kinderbetreuung einführen. Daneben untersuchen wir den Einfluss der Bildung auf das Lohnprofil. Wir schätzen die Mincer-Koeffizienten für 12 westeuropäische Länder mit den EU-SILC-Daten für 2007 und nutzen sie als Input zur Kalibrierung eines Modells des Optimierungsproblem eines Individuums. Schließlich analysieren wir die Auswirkung und Relevanz verschiedener Politikbereiche. Insbesondere schätzen wir die Elastizitäten der Bildungserträge im Hinblick auf Änderungen der Arbeitslosenunterstützung, der marginalen und durchschnittlichen Steuersätze und Leistungen bei Mutterschaft und für Kinderbetreuung.
Keywords: I21; 330; human capital; rate of return; public policy; Bildungsertrag; Lohndifferenzierung; Familienpolitik; Schätzung; Westeuropa